2006
DOI: 10.1002/jat.1176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methyl paraben on skin keratinocytes

Abstract: Some ingredients of dermatological formulations result in skin irritation and allergy. In particular, preservatives have been reported extensively as a cause of allergic contact dermatitis. The study focused on parabens which have been used extensively as antimicrobial preservatives in foods, drugs and cosmetics. The aim of this study was to clarify the effects of the daily use of methyl paraben (MP) on human skin.The concentrations of MP in the stratum corneum (SC) of the human forearm were measured using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 23 publications
2
69
0
2
Order By: Relevance
“…It is reported that PHBA can also cause physiological estrogenic responses (Boberg et al 2010;Dobbins et al 2009;Gonzalez-Doncel et al 2014). Although it is less toxic than parabens (Ishiwatari et al 2007), the relative high level of PHBA in swimming pools cannot be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that PHBA can also cause physiological estrogenic responses (Boberg et al 2010;Dobbins et al 2009;Gonzalez-Doncel et al 2014). Although it is less toxic than parabens (Ishiwatari et al 2007), the relative high level of PHBA in swimming pools cannot be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…Whether such an in½uence is positive or negative at different life stages and at different concentrations needs urgent investigation. Recent research has reported that methylparaben can indeed in½uence the aging and differentiation of keratinocytes (Ishiwatari et al, 2007), since long-term application of methylparaben to keratinocytes could in½uence proliferation rate, cell morphology and expression of hyaluronan synthases and type IV collagen. Further work has shown that methylparaben and ethylparaben can induce oxidative stress in skin after reaction with singlet oxygen ( 1 O 2 ) in visible light to produce glutathione conjugates of hydroquinone (Nishizawa et al, 2006).…”
Section: Parabens and Skin Cancermentioning
confidence: 99%
“…In vitro models suggest the potential for accumulation in underlying regions of skin (Ishiwatari et al, 2007), and recent unpublished data were broadcast on UK television (screened 11 October 2007. http://www.unrealitytv.co.uk/reality-tv/beauty-addicts-howtoxic-are-you-channel-4) indicating that body burdens of parabens could be reduced by eradicating use of cosmetics containing parabens. The ability to reduce body burden through alteration to cosmetic exposure needs to be substantiated by a controlled scienti¼c study in a statistically viable group of subjects.…”
Section: Conclusion and Further Research Neededmentioning
confidence: 99%
See 1 more Smart Citation
“…The osterogenic effects of parabens have been confirmed in 1998 (Routledge et al, 1998). Also topical daily administration of parabens decreased the keratinocytes proliferation and cell morphology (Ishiwatari et al, 2007). On the basis of research, the oesterogenic stimulation is associated with female breast cancer incidence and development of malignant melanoma in male reproductive system (Darbre & Harvey, 2008;Tavares et al, 2009).…”
Section: Introductionmentioning
confidence: 97%